Regulation of ROS Metabolism in Plants under Environmental Stress: A Review of Recent Experimental Evidence - Hasanuzzaman, Mirza; Bhuyan, M. H. M. Borhannuddin; Parvin, Khursheda; Bhuiyan, Tasnim Farha; Anee, Taufika Islam; Nahar, Kamrun; Hossen, Md. Shahadat; Zulfiqar, Faisal; Alam, Md. Mahabub; Fujita, Masayuki (International journal of molecular sciences, 2020)
Various environmental stresses singly or in combination generate excess amounts of reactive oxygen species (ROS), leading to oxidative stress and impaired redox homeostasis. Generation of ROS is the obvious outcome of abiotic stresses and is gaining importance not only for their ubiquitous generation and subsequent damaging effects in plants but also for their diversified roles in signaling cascade, affecting other biomolecules, hormones concerning growth, development, or regulation of stress tolerance. Therefore, a good balance between ROS generation and the antioxidant defense system protects photosynthetic machinery, maintains membrane integrity, and prevents damage to nucleic acids and proteins. Notably, the antioxidant defense system not only scavenges ROS but also regulates the ROS titer for signaling. A glut of studies have been executed over the last few decades to discover the pattern of ROS generation and ROS scavenging. Reports suggested a sharp threshold level of ROS for being beneficial or toxic, depending on the plant species, their growth stages, types of abiotic stresses, stress intensity, and duration. Approaches towards enhancing the antioxidant defense in plants is one of the vital areas of research for plant biologists. Therefore, in this review, we accumulated and discussed the physicochemical basis of ROS production, cellular compartment-specific ROS generation pathways, and their possible distressing effects. Moreover, the function of the antioxidant defense system for detoxification and homeostasis of ROS for maximizing defense is also discussed in light of the latest research endeavors and experimental evidence.